2004
DOI: 10.1111/j.0022-202x.2004.22621.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Sphingomyelinase Activity and Epidermal Differentiation in Atopic Dermatitis

Abstract: A defective permeability barrier leads to the penetration of environmental allergens into the skin and initiates immunological reactions and inflammation crucially involved in the pathogenesis of atopic dermatitis (AD). Decreased stratum corneum ceramide content may cause the defect in permeability barrier function consistently found in AD. Acid and neutral sphingomyelinase (A- and N-SMase) generate ceramides with structural and signal transduction functions in epidermal proliferation and differentiation. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
268
4
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(314 citation statements)
references
References 78 publications
(66 reference statements)
32
268
4
10
Order By: Relevance
“…This is contradictory to previous studies by Sugiara et al [28] and Jensen et al [29]. Using gene microarrays, Sugiara et al [28] observed increased IVL and decreased LOR gene expression in lesional AD skin.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This is contradictory to previous studies by Sugiara et al [28] and Jensen et al [29]. Using gene microarrays, Sugiara et al [28] observed increased IVL and decreased LOR gene expression in lesional AD skin.…”
Section: Discussionmentioning
confidence: 65%
“…This factor is not clearly defined in either of the previous studies [28,29]. AD lesions are bi-phasic with acute lesions having more of a Th2 cytokine milieu and chronic lesions having more of a Th1 cytokine milieu [19].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…LTA activated IDECs migrate to draining lymph nodes of skin to promote Th1 responses permeability barrier may be a result of an altered lipid composition, such as decreased ceramide, in the stratum corneum (SC). 26 Ceramides are major water retaining molecules present in the extracellular space of the cornified envelope. During the process of cornification, the ceramide containing bilayer is covalently attached to various proteins on the extracellular surface of the cornified envelope.…”
Section: Skin Barrier Dysfunctionmentioning
confidence: 99%
“…28 The mechanisms by which the ceramide content is altered include the decreased activity of epidermal acid sphingomyelinase (A-SMase) in lesional and non lesional skin which correlates with reduced SC ceramide content and defects in permeability barrier. 26 Recent studies have demonstrated that stress, which is a known exacerbator for AD, can have direct effects on skin barrier properties. Reports have demonstrated that insomniac psychologic stress affects epidermal cell proliferation, impairs epidermal differentiation and reduces the formation of lamellar bodies (LB) ultimately resulting in reduced synthesis of epidermal lipids such as cholesterol, fatty acid and ceramides.…”
Section: Skin Barrier Dysfunctionmentioning
confidence: 99%